Reducing transverse motion of marine risers with actuator dynamics by boundary control - Do, Khac Duc; Pan, J. (2008)
This paper presents a boundary controller to reduce transverse motion of flexible marine risers driven by a hydraulic system at the top end of the risers under environmental disturbances. The boundary controller is designed based on Lyapunov's direct method and the backstepping technique. Proof of existence and uniqueness of the solutions of the closed loop control system is carried out by using the Galerkin approximation method. © 2008 IEEE.